2020
DOI: 10.1098/rspb.2020.1447
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific variation in the use of vertical habitat by a resident Antarctic top predator

Abstract: Patterns of habitat use are commonly studied in horizontal space, but this does not capture the four-dimensional nature of ocean habitats (space, depth, and time). Deep-diving marine animals encounter varying oceanographic conditions, particularly at the poles, where there is strong seasonal variation in vertical ocean structuring. This dimension of space use is hidden if we only consider horizontal movement. To identify different diving behaviours and usage patterns of vertically distributed habitat, we use h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 66 publications
1
16
4
Order By: Relevance
“…Both the female and the three males in our study displayed a mixture of pelagic and benthic dives; however, pelagic dives were more common that benthic dives for both sexes. This is in contrast to what Photopoulou et al (2020) found, where males performed only benthic dives on the shelf and females left the shelf and moved northward. We found no obvious sex-specific differences nor any seasonal shifts in behaviour, but given that our sample size was small, this conclusion is not definitive.…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…Both the female and the three males in our study displayed a mixture of pelagic and benthic dives; however, pelagic dives were more common that benthic dives for both sexes. This is in contrast to what Photopoulou et al (2020) found, where males performed only benthic dives on the shelf and females left the shelf and moved northward. We found no obvious sex-specific differences nor any seasonal shifts in behaviour, but given that our sample size was small, this conclusion is not definitive.…”
Section: Discussioncontrasting
confidence: 96%
“…hunting time per dive) was the greatest. This is a novel observation and in contrast to the earlier findings from the Weddell Sea (Nachtsheim et al 2019, Photopoulou et al 2020). Seals were found within the outflow, at the mouth of the trough, over the sill or travelling N-S over the central part or over the eastern side at the boundary of ISW or within it.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations